ETHICAL BUSINESS IMPLEMENTATION OF CORPORATE GOVERNANCE: GOOD CORPORATE REPUTATION - Wardani, Mellinda Sri; Putri, Cut Nurul Tasya; Bukti, Rina Br. (jfpublisher, 2023)
Ethical codes are guidelines of principles that are designed to assist professionals in conducting business with honesty and integrity. Ethical codes may include categories such as business ethics, professional codes of conduct, and employee codes of conduct. Ethical codes are important because it clearly defines behavioral rules and provides a basis for early caution. Therefore, this research is conducted to examine the implementation of business ethics in corporate governance can generate a good reputation. This research used descriptive qualitative approach combined with literature study. The literature study used is collecting data, such as references to journal articles, books, and online documentation related to the application of business ethics in corporate governance as supporting material in writing this research. The main finding of this research is the importance of business ethics in corporate governance, such as integrity, honesty, equity, responsibility and creating good working relationships, which have an impact on improving the company's operational activities in making profits.